PENGARUH EKSPOR TERHADAP CADANGAN DEVISA INDONESIA TAHUN 2001-2020 - Guampe, Feliks Arfid; Lamintu, Femi Krisdiyanti; Kayupa, Olvit Olniwati (ANALISIS, 2023)
This study aims to analyze the effect of exports on Indonesia's foreign exchange reserves in 2001-2020. This research is included in quantitative research using secondary data. Data analysis using a simple linear regression method using SPSS 26. The results showed that exports had a positive and significant effect on the level of Indonesia's foreign exchange reserves in 2001-2020. The level of determination shows that exports can explain foreign exchange reserves of 28.6% while the remaining 71.4% is explained by other variables outside this study.